Exploration of the Influence of Big Five Personality Traits on Innovative Behavior - Suciana, Frisca; Mansyur, Anwar (Manunggal Halim Jaya, 2025)
This study aims to analyze the relationship between Big Five Personality and innovative work behavior case study from Liquid Petroleum Gas (LPG) depot owners and employees in Tegal Regency, Indonesia. This study uses a quantitative approach with the correlational design method, while the data analysis technique includes instrument testing consisting of validity and reliability tests. After the instrument test, model and hypothesis testing were carried out to analyze the data. Data was collected through an e-survey using Google Forms and distributed to various LPG depots in the Tegal Regency. The research sample used a purposive sampling technique of 153 respondents selected to represent the population. This study lasted two months, from October to November 2024, to better understand the factors influencing innovative behavior in LPG distribution. The hypothesis test results showed that of the five dimensions of Big Five Personality, only Conscientiousness and Agreeableness significantly influence Innovative Work Behavior, with a value of t = 2.536, Sig. = 0.012 for Conscientiousness and t = 2.268, Sig. = 0.025 for Agreeableness. Meanwhile, Openness to Experience (t = 0.469, Sig. = 0.640), Extraversion (t = -0.812, Sig. = 0.418), and Neuroticism (t = 0.809, Sig. = 0.420) do not have a significant effect on Innovative Work Behavior because their significance values are greater than 0.05. Thus, not all personality dimensions have a significant role in encouraging innovative work behavior.